Poliska and Tauromee, Riley County - Bohn, Jeremy (Kansas State University, The Chapman Center for Rural Studies, 2013)
This is a study of Poliska and Tauromee, Kansas. These two towns, in the vicinity of Manhattan, Kan., only lasted two-three years, due to several factors, including the ever-growing city of Manhattan, which basically sucked both towns in. This study uses early maps, field work, and early histories of Manhattan.
Jeremy Bohn, “Poliska and Tauromee, Riley County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/112.
Keywords: Fort Leavenworth/Fort Riley Trail; Juniata; Kansas River; Poliska; Rocky Ford; Riley County